2018
DOI: 10.1002/ange.201810225
|View full text |Cite
|
Sign up to set email alerts
|

A Water‐Splitting Carbon Nitride Photoelectrochemical Cell with Efficient Charge Separation and Remarkably Low Onset Potential

Abstract: As imple method to growaclosely packed carbon nitride (CN) film by the crystallization of CN monomers on ac onductive substrate followed by at hermal condensation is reported. The as-synthesized CN exhibits excellent performance as photoanode material in aphotoelectrochemical cell. Detailed (photo)electrochemical and transient absorption measurements indicate excellent charge separation properties, high hole-extraction efficiency (up to 50 %), al ong electron lifetime,a nd low amount of defect states belowt he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…The presence of shallow and deep trap states can also be inferred from different decay kinetics of photoinduced absorptions in the visible and NIR regions 112,[119][120][121] . The presence of trap states can also be inferred from red-shifted electroluminescence compared to the PL of CN x H y thin films 7 and electrons with millisecond lifetimes have been observed in CN x H y photoelectrodes 122,123 . A successful strategy to prevent charge trapping into inactive states has been demonstrated by introducing additional components such as red phosphorous crystals 124 , boron 28 , or TiO 2 mesocrystals 125 , thus enabling rapid charge extraction that effectively competes with charge trapping.…”
Section: Carbon Nitride Photophysicsmentioning
confidence: 99%
“…The presence of shallow and deep trap states can also be inferred from different decay kinetics of photoinduced absorptions in the visible and NIR regions 112,[119][120][121] . The presence of trap states can also be inferred from red-shifted electroluminescence compared to the PL of CN x H y thin films 7 and electrons with millisecond lifetimes have been observed in CN x H y photoelectrodes 122,123 . A successful strategy to prevent charge trapping into inactive states has been demonstrated by introducing additional components such as red phosphorous crystals 124 , boron 28 , or TiO 2 mesocrystals 125 , thus enabling rapid charge extraction that effectively competes with charge trapping.…”
Section: Carbon Nitride Photophysicsmentioning
confidence: 99%
“…As CN MW-ins contained more M2 than bulk CN, it indicated that M2 may play an essential role in accelerating the charge separation. In this sense, the hole- and electron-extraction properties were evaluated by measuring anodic and cathodic photocurrents, respectively, in the presence of an electron donor (triethanolamine, TEOA), assuming the maximum photocurrent can be obtained without any hole- or electron-transfer limitations 51 , 52 . As shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[22,23] In the case of a better stacking order of the graphitic layers, a hole extraction efficiency of ~47% was obtained. [24] However, in all the abovementioned scenarios, only one problem was tackled either ediffusion or h + extraction due to synthetic limitations. Therefore, a new CN electrode design, which enables achieving both better ediffusion and enhanced h + extraction efficiency is needed for a substantial improvement in performance.…”
mentioning
confidence: 99%